Identification of Risk of Damage in the Procedure of Peripheral Venipuncture Performed by Nurses: A Scope Review Protocol (Research, Society and Development, 2021)
It is a scope review protocol about invasive procedures performed by nurses, and aims to formalize the primary study. The protocol defines the methodology that will be adopted, which is based on guidelines from the Joanna Briggs Institute through the following phases: Elaboration the research question; Construction of the review protocol; Search of publications in electronic databases; Selection of articles; Extraction of data from articles and Synthesis and Analysis of data. With the review, it is expected to promote patient safety and identify risks and adverse events in peripheral venous punctures, performed by nurses.